2000
DOI: 10.1054/bjoc.2000.1317
|View full text |Cite
|
Sign up to set email alerts
|

The association between atypical adenomatous hyperplasia and primary lung cancer

Abstract: Summary Atypical adenomatous hyperplasia (AAH) has been suggested as the adenoma in an adenoma-carcinoma sequence in the lung periphery. From 1989-1998, we undertook a systematic, prospective search for AAH in lungs resected for cancer. AAH was found in 67 of 554 patients (12.1%) with primary lung carcinoma (9.2% in male patients and 19.0% in females). AAH was found in lungs bearing adenocarcinoma (23.2%) more frequently than with large cell undifferentiated carcinoma (12.5%) or squamous carcinoma (3.3%). A gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
66
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(71 citation statements)
references
References 28 publications
5
66
0
Order By: Relevance
“…Weng et al also reported that there is no definite correlation between smoking history and the occurrence of AAH. In contrast, Chapman and Kerr (36) have recently demonstrated that a greater percentage of women with adenocarcinoma had AAH (30.2%) than did men with adenocarcinoma (18.8%).…”
Section: Epidemiologymentioning
confidence: 86%
See 1 more Smart Citation
“…Weng et al also reported that there is no definite correlation between smoking history and the occurrence of AAH. In contrast, Chapman and Kerr (36) have recently demonstrated that a greater percentage of women with adenocarcinoma had AAH (30.2%) than did men with adenocarcinoma (18.8%).…”
Section: Epidemiologymentioning
confidence: 86%
“…Miller (26) examined 247 cases of surgically resected lung carcinomas by sectioning all areas of the lung transversely at 1.0-to 1.5-cm intervals and found 23 (9.3%) of lesions to be what she called bronchioloalveolar cell adenomas. Other investigators have reported a frequency of AAH of 5 to 20% in surgically resected lungs for pulmonary carcinoma (20,(32)(33)(34)(35)(36). Weng et al (32) reviewed the literature that examined the incidence of AAH and found that it was notably higher in specimens obtained from patients with primary lung carcinoma (20.0%) than in those with nonprimary lung carcinoma (4.8%).…”
Section: Epidemiologymentioning
confidence: 99%
“…These lesions resemble human atypical adenomatous hyperplasia, which is considered a precursor lesion to lung adenocarcinoma. 19 In mouse gene-targeting models where lung tumorigenesis is caused by somatic K-ras2 activation (mutation), massive alveolar hyperplasia/dysplasia precedes tumor development, 20,21 indicating that these early morphologic alterations are caused by K-ras2 mutations. Accordingly, K-ras2 mutations have been reported in both human and carcinogen-induced mouse lung hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
“…2 Adenocarcinoma is considered to develop by a pathway of atypical adenomatous hyperplasia and bronchioloalveolar carcinoma. [2][3][4] However, whether atypical adenomatous hyperplasia-bronchioloalveolar carcinoma pathway is really the only pathway for pulmonary adenocarcinoma has been questioned on the basis of a number of observations. 5 First, atypical adenomatous hyperplasias are not as common as adenocarcinomas with features of bronchioloalveolar carcinoma or premalignant lesions in other organs.…”
mentioning
confidence: 99%